Community knowledge on dengue in territories under risk in the state of São Paulo - Pereira, Leyde Emanuelle Costa [UNESP]; Ferreira, Elka Machado [UNESP]; Picinato, Mirelle Andréa De Carvalho [UNESP]; Mathias, Luís Antonio [UNESP]; Arcêncio, Ricardo Alexandre; Barbosa, Kamilla Fagundes Duarte; Ferraudo, Antonio Sergio [UNESP] (Instituto Biológico, 2022)
In the last decades, the global incidence of arboviruses transmitted by the vector Aedes aegypti has increased dramatically with the increased oh human mobility and urbanization. The study of the mosquito population is of great importance for public health in countries where climatic and environmental conditions are favorable for the spread of these diseases transmitted by A. aegypti. This was a cross-sectional study that assessed causal relationships between why mosquitoes are prevalent in the region studied and socioeconomic variables, practices, knowledge, attitudes, and the effect of the cause in two regions chosen according to vulnerability (São Paulo Social Vulnerability Index). Of the 435 residents interviewed, 95% (413/435) were informed about vector control and claimed to contribute to the day-to-day sanitary practices necessary to combat it, in addition to being able to identify it. Most participants in both regions believed they were at risk, but vector control practices did not match those recorded in the survey. A correlation was found between the population’s level of education and the practices observed. Despite the high levels of knowledge and the perceptions of the interviewed population about A. aegypti, the erroneous behavior of the residents persisted, thus hindering disease prevention and vector control actions, promoting the conditions conducive to the proliferation of the vector, and, consequently, increasing the risk of disease. The study indicated that one of the most effective means to control the A. aegypti vector is a society informed about preventive measures in the surveillance sectors.
Keywords: Aedes aegypti; epidemiology; insect vectors